Pengaruh Kompetensi SDM, SPIP, Dan Pemanfaatan TI Terhadap Kualitas Laporan Keuangan Pemerintah Daerah Dengan Komitmen Organisasi Sebagai Variabel Moderating Pada OPD Kota Tanjung Balai - fikri, Rizal; Astuty, Widia; Sari, Maya (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The aim of this research is to determine and analyze the factors that influence the quality of financial reports in the Tanjung Balai City Government. The influencing factors are human resource competency, internal control systems, and use of information technology, with organizational commitment as the moderating variable. The type of research in this research is quantitative research using primary data and data collection techniques through distributing questionnaires to the Regional Apparatus Organizations of Tanjung Balai City, North Sumatra, Indonesia. The sampling method is using the census method, so that the entire population is used as the research sample. The population of this study was 34 OPDs, each consisting of 3 respondents with a total of 102 respondents. The data was processed using the SEM method with the help of the Smart PLS analysis tool. The results of this research prove that human resource competency influences the quality of the Tanjung Balai City Government's financial reports, the government's internal control system influences the quality of the Tanjung Balai City Government's financial reports, the use of information technology influences the quality of the Tanjung Balai City Government's financial reports. Organizational commitment can moderate the respective influences of human resource competence, internal control systems, and the use of information technology on the quality of the Tanjung Balai City regional government's financial reports.